Late Pleistocene-Holocene sequence stratigraphy of the subaqueous Red River delta and the adjacent shelf - Thanh, Nguyen Trung; Liu, Paul Jing; Dong, Mai Duc; Nhon, Dang Hoai; Cuong, Do Huy; Dung, Bui Viet; Phach, Phung Van; Thanh, Tran Duc; Hung, Duong Quoc; Nga, Ngo Thanh (Vietnam Journal of Earth Sciences, 2018)
The model of Late Pleistocene-Holocene sequence stratigraphy of the subaqueous Red River delta and the adjacent shelf is proposed by interpretation of high-resolution seismic documents and comparison with previous research results on Holocene sedimentary evolution on the delta plain. Four units (U1, U2, U3, and U4) and four sequence stratigraphic surfaces (SB1, TS, TRS and MFS) were determined. The formation of these units and surfaces is related to the global sea-level change in Late Pleistocene-Holocene. SB1, defined as the sequence boundary, was generated by subaerial processes during the Late Pleistocene regression and could be remolded partially or significantly by transgressive ravinement processes subsequently. The basal unit U1 (fluvial formations) within incised valleys is arranged into the lowstand systems tract (LST) formed in the early slow sea-level rise 19-14.5 cal.kyr BP, the U2 unit is arranged into the early transgressive systems tract (E-TST) deposited mainly within incised-valleys under the tide-influenced river to estuarine conditions in the rapid sea-level rise 14.5-9 cal.kyr BP, the U3 unit is arranged into the late transgressive systems tract (L-TST) deposited widely on the continental shelf in the fully marine condition during the late sea-level rise 9-7 cal.kyr BP, and the U4 unit represents for the highstand systems tract (HST) with clinoform structure surrounding the modern delta coast, extending to the water depth of 25-30 m, developed by sediments from the Red River system in 3-0 cal.kyr BP. References Badley M.E., 1985. Practical Seismic Interpretation. International Human Resources Development Corporation, Boston, 266p. Bergh G.D. V.D., Van Weering T.C.E., Boels J.F., Duc D.M, Nhuan M.T, 2007. Acoustical facies analysis at the Ba Lat delta front (Red River delta, North Vietnam. Journal of Asian Earth Science, 29, 532-544. Boyd R., Dalrymple R., Zaitlin B.A., 1992. Classification of Elastic Coastal Depositional Environments. Sedimentary Geology, 80, 139-150. Catuneanu O., 2002. Sequence stratigraphy of clastic systems: concepts, merits, and pitfalls. Journal of African Earth Sciences, 35, 1-43. Catuneanu O., 2006. Principles of Sequence Stratigraphy. Elsevier, Amsterdam, 375p. Catuneanu O., Abreu V., Bhattacharya J.P., Blum M.D., Dalrymple R.W., Eriksson P.G., Fielding C.R., Fisher W.L., Galloway W.E., Gibling M.R., Giles K.A., Holbrook J.M., Jordan R., Kendall C.G. St. C., Macurda B., Martinsen O.J., Miall A.D., Neal J.E., Nummedal D., Pomar L., Posamentier H.W., Pratt B.R., Sarg J.F., Shanley K.W., Steel R. J., Strasser A., Tucker M.E., Winker C., 2009. Towards the standardization of sequence stratigraphy. Earth-Science Reviews, 92, 1-33. Catuneanu O., Galloway W.E., Kendall C.G. St C., Miall A.D., Posamentier H.W., Strasser A. and Tucker M.. E., 2011. Sequence Stratigraphy: Methodology and Nomenclature. Newsletters on Stratigraphy, 44(3), 173-245. Coleman J.M and Wright L.D., 1975. Modern river deltas: variability of processes and sand bodies. In: Broussard M.L (Ed), Deltas: Models for exploration. Houston Geological Society, Houston, 99-149. Doan Dinh Lam, 2003. History of Holocene sedimentary evolution of the Red River delta. PhD thesis in Vietnam, 129p (in Vietnamese). Duc D.M., Nhuan M.T, Ngoi C.V., Nghi T., Tien D.M., Weering J.C.E., Bergh G.D., 2007. Sediment distribution and transport at the nearshore zone of the Red River delta, Northern Vietnam. Journal of Asian Earth Sciences, 29, 558-565. Dung B.V., Stattegger K., Unverricht D., Phach P.V., Nguyen T.T., 2013. Late Pleistocene-Holocene seismic stratigraphy of the Southeast Vietnam Shelf. Global and Planetary Change, 110, 156-169. Embry A.F and Johannessen E.P., 1992. T-R sequence stratigraphy, facies analysis and reservoir distribution in the uppermost Triassic-Lower Jurassic succession, western Sverdrup Basin, Arctic Canada. In: Vorren T.O., Bergsager E., Dahl-Stamnes O.A., Holter E., Johansen B., Lie E., Lund T.B. (Eds.), Arctic Geology and Petroleum Potential. Special Publication. Norwegian Petroleum Society (NPF), 2, 121-146. Funabiki A., Haruyama S., Quy N.V., Hai P.V., Thai D.H., 2007. Holocene delta plain development in the Song Hong (Red River) delta, Vietnam. Journal of Asian Earth Sciences, 30, 518-529. General Department of Land Administration., 1996. Vietnam National Atlas. General Department of Land Administration, Hanoi, 163p. Hanebuth T.J.J. and Stattegger K., 2004. Depositional sequences on a late Pleistocene-Holocene tropical siliciclastic shelf (Sunda shelf, Southeast Asia). Journal of Asian Earth Sciences, 23, 113-126. Hanebuth T.J.J., Voris H.K.., Yokoyama Y., Saito Y., Okuno J., 2011. Formation and fate of sedimentary depocenteres on Southeast Asia’s Sunda Shelf over the past sea-level cycle and biogeographic implications. Eath-Science Reviews, 104, 92-110. Hanebuth T., Stattegger K and Grootes P. M., 2000. Rapid flooding of the Sunda Shelf: a late-glacial sea-level record. Science, 288, 1033-1035. Helland-Hansen W and Gjelberg, J.G., 1994. Conceptual basis and variability in sequence stratigraphy: a different perspective. Sedimentary Geology, 92, 31-52. Hori K., Tanabe S., Saito Y., Haruyama S., Nguyen V., Kitamura., 2004. Delta initiation and Holocene sea-level change: example from the Song Hong (Red River) delta, Vietnam. Sedimentary Geology, 164, 237-249. Hunt D. and Tucker M.E., 1992. Stranded parasequences and the forced regressive wedge systems tract: deposition during base-level fall. Sedimentology Geology, 81, 1-9. Hunt D. and Tucker M.E., 1995. Stranded parasequences and the forced regressive wedge systems tract: deposition during base-level fall-reply. Sedimentary Geology, 95, 147-160. Lam D.D. and Boyd W.E., 2000. Holocene coastal stratigraphy and model for the sedimentary development of the Hai Phong area in the Red River delta, north Vietnam. Journal of Geology (Series B), 15-16, 18-28. Lieu N.T.H., 2006. Holocene evolution of the Central Red River Delta, Northern Vietnam. PhD thesis of lithological and mineralogical in Germany, 130p. Luu T.N.M., Garnier J., Billen G., Orange D., Némery J., Le T.P.Q., Tran H.T., Le L.A., 2010. Hydrological regime and water budget of the Red River Delta (Northern Vietnam). Journal of Asian Earth Sciences, 37, 219-228. Mather S.J., Davies J., Mc Donal A., Zalasiewicz J.A., and Marsh S., 1996. The Red River Delta of Vietnam. British Geological Survey Technical Report WC/96/02, 41p. Mathers S.J. and Zalasiewicz J.A.,1999. Holocene sedimentary architecture of the Red River delta, Vietnam. Journal of Coastal Research, 15, 314-325. Milliman J.D. and Mead R.H., 1983. Worldwide delivery of river sediment to the oceans. Journal of Geology, 91, 1-21. Milliman J.D and Syvitski J.P.M., 1992. Geomorphic/tectonic control of sediment discharge to the Ocean: the importance of small mountainous rivers. Journal of Geology, 100, 525-544. Mitchum Jr. R.M., Vail P.R., 1977. Seismic stratigraphy and global changes of sea-level. Part 7: stratigraphic interpretation of seismic reflection patterns in depositional sequences. In: Payton C.E. (Ed.), Seismic Stratigraphy-Applications to Hydrocarbon Exploration, A.A.P.G. Memoir, 26, 135-144. Nguyen T.T., 2017. Late Pleistocene-Holocene sedimentary evolution of the South East Vietnam Shelf, PhD thesis (in Vietnamese), Hanoi University of Science, Vietnam, 169p. Nummedal D., Riley G.W., Templet P.T., 1993. High-resolution sequence architecture: a chronostratigraphic model based on equilibrium profile studies. In: Posamentier H.W., Summerhayes C.P., Haq B.U., Allen G.P. (Eds.), Sequence stratigraphy and Facies Associations. International Association of Sedimentologists Special Publication, 18, 55-58. Posamentier H.W. and Allen G.P., 1999. Siliciclastic sequence stratigraphy: concepts and applications. SEPM Concepts in Sedimentology and Paleontology, 7, 210p. Posamentier H.W., Jervey M.T. and Vail P.R., 1988. Eustatic controls on clastic deposition I-Conceptual framework. Sea-level changes-An Integrated Approach, The Society of Economic Paleontologists and Mineralogist. SEPM Special Publication, 42, 109-124. Reineck H.E., Singh I.B., 1980. Depositional sedimentary environments with reference to terrigenous clastics. Springer-Verlag Berlin Heidelberg New York, 551p. Ross K., 2011. Fate of Red River Sediment in the Gulf of Tonkin, Vietnam. Master Thesis. North Carolina State University, 91p. Saito Y., Katayama H., Ikehara K., Kato Y., Matsumoto E., Oguri K., Oda M., Yumoto M. 1998. Transgressive and highstand systems tracts and post-glacial transgression, the East China Sea. Sedimentary Geology, 122, 217-232. Stattegger K., Tjallingii R., Saito Y., Michelli M., Nguyen T.T., Wetzel A., 2013. Mid to late Holocene sea-level reconstruction of Southeast Vietnam using beachrock and beach-ridge deposits. Global and Planetary Change, 110, 214-222. Tanabe S., Hori K., Saito Y., Haruyama S., Doanh L.Q., Sato Y., Hiraide S., 2003a. Sedimentary facies and radiocarbon dates of the Nam Dinh-1 core from the Song Hong (Red River) delta, Vietnam. Journal of Asian Earth Sciences, 21, 503-513. Tanabe S., Hori K., Saito Y., Haruyama S., Phai V.V., Kitamura A., 2003b. Song Hong (Red River) delta evolution related to millennium-scale Holocene sea-level changes. Quaternary Science Reviews, 22(21-22), 2345-2361. Tanabe S., Saito Y., Lan V.Q., Hanebuth T.J.J., Lan N.Q., Kitamura A., 2006. Holocene evolution of the Song Hong (Red River) delta system, northern Vietnam. Sedimentary Geology, 187, 29-61. Thanh T.D. and Huy D.V., 2000. Coastal development of the modern Red River Delta. Bulletin of the Geological Survey of Japan, 5, 276. Tjallingii R., Stattegger K., Wetzel A., Phung VP., 2010. Infilling and flooding of the Mekong River incised valley during deglacial sea-level rise. Quaternary Science Reviews, 29, 1432-1444. Vail P.R., 1987. Seismic stratigraphy interpretation procedure. In: Bally, A.W. (Ed), Atlats of Seismic Stratigraphy. American Association of Petroleum Geologist Studies in Geology, 27, 1-10. Van Wagoner J.C., Posamentier H.W., Mitchum R.M., Vail P.R., Sarg P.R., Louit J.F., Hardenbol J., 1988. An overview of the fundamental of sequence stratigraphy and key definitions. An Integrated Approach, SEPM Special Publication, 42, 39-45. Veeken P.C.H., 2006. Seismic stratigraphy Basin Analysis and Reservoir Characterization. Handbook of geophysical exploration, Elsevier, Oxford, 37509p. Yoo D.G., Kim S.P., Chang T.S., Kong G.S., Kang N.K., Kwon Y.K., Nam S.L., Park S.C., 2014. Late Quaternary inner shelf deposits in response to late Pleistocene-Holocene sea-level changes: Nakdong River, SE Korea. Quaternary International, 344, 156-169.